2020
DOI: 10.1029/2020wr028565
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Numerical Modeling of Compound Flooding Caused by Tropical Storm Matthew Over a Data‐Scarce Coastal Environment

Abstract: The passage of a tropical storm, as the main driver of storm surge and high waves in many coastal regions, can also generate heavy rainfall and cause river overflow. The resulting combination of riverine, pluvial, and coastal flood hazard can result in catastrophic losses particularly in densely populated coastal environments. In this study, we characterize compound flooding caused by Tropical Storm Matthew and assess the significance and associated uncertainties of multiple contributing factors over a data-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 87 publications
(105 reference statements)
0
10
0
Order By: Relevance
“…• projecting the risk of compound extremes for different levels of future warming (Zscheischler et al, 2018;Wang et al, 2020); • evaluating the impacts of the compound extremes on natural and built environments (AghaKouchak et al, 2020;Zhang and Najafi, 2020); • developing adaptation measures to the changing risk of compound extremes (Weber et al, 2020;Clarke et al, 2021); • enhancing subseasonal-to-seasonal prediction of these extremes (Zamora et al, 2021;Zou, 2021); • improving the representation and evaluation of compound extremes in fully-coupled climate models (Ridder et al, 2021;Zscheischler et al, 2021) and developing multivariate bias correction for these models (Vezzoli et al, 2017;Zscheischler et al, 2019); • applying machine learning to understand these extremes Zou, 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• projecting the risk of compound extremes for different levels of future warming (Zscheischler et al, 2018;Wang et al, 2020); • evaluating the impacts of the compound extremes on natural and built environments (AghaKouchak et al, 2020;Zhang and Najafi, 2020); • developing adaptation measures to the changing risk of compound extremes (Weber et al, 2020;Clarke et al, 2021); • enhancing subseasonal-to-seasonal prediction of these extremes (Zamora et al, 2021;Zou, 2021); • improving the representation and evaluation of compound extremes in fully-coupled climate models (Ridder et al, 2021;Zscheischler et al, 2021) and developing multivariate bias correction for these models (Vezzoli et al, 2017;Zscheischler et al, 2019); • applying machine learning to understand these extremes Zou, 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For example, a global river routing model forced by global hydrological models and bounded downstream by a global tide and surge model has been used to assess the effect of storm surge on riverine flood (Eilander et al, 2020). Hydrologic and hydrodynamic models are combined to assess compound flooding caused by the 2016 tropical storm Matthew (Zhang and Najafi, 2020). In addition, joint probabilities and copula have been widely used to examine the compounds (Czajkowski et al, 2013;Petroliagkis et al, 2016;Couasnon et al, 2018).…”
Section: Storm Surge and Riverine Floodsmentioning
confidence: 99%
“…To improve the investment options in preparedness, researchers in [43] developed a restoration map and a suite of infrastructure asset damage that will consider the infrastructure interdependencies. Study [44] concluded that a small number of methods have been proposed to model interdependencies among substations (S/Ss) in electric power systems. For this reason, the authors proposed a solution that offers a practical tool for decision-makers to distinguish between S/Ss and their mutual associations, which enables them to identify the critical S/Ss.…”
Section: Systematic Literature Surveymentioning
confidence: 99%
“…These analyses include characterizing the statistical interrelationships between drivers of flooding based on Bayesian networks (Couasnon et al., 2018; Sebastian et al., 2017), copula theory (Bevacqua et al., 2017; Gori et al., 2020; Moftakhari et al., 2017; Paprotny et al., 2018; Xu et al., 2014), bivariate extreme value distributions (Zheng et al., 2014), correlation and linear regression (Robins et al., 2021), bivariate logistic threshold‐excess model (Zheng et al., 2013) among others. Besides, recent studies have assessed the compound flood impacts and risks through process‐based modeling and hybrid statistical‐dynamical framework (Ganguli et al., 2020; Ganguli & Merz, 2019; Najafi et al., 2021; Wang et al., 2021; Zhang & Najafi, 2020).…”
Section: Introductionmentioning
confidence: 99%